Effects of Monensin and Rapamycin Combination Therapy on Tumor Growth and Apoptosis in a Xenograft Mouse Model of Neuroblastoma - Sema Serter Kocoglu; Fatma Bahar Sunay; Pakize Nur Akkaya (MDPI AG, 2023)
Neuroblastoma is the most common pediatric solid tumor originating from the neural crest. New treatment options are needed to improve treatment outcomes and the survival of patients with neuroblastoma. Monensin is an ionophore antibiotic with antiparasitic, antibacterial, and anticancer properties isolated from Streptomyces cinnamonensis. The aim of this study was to investigate the therapeutic effects of single and combined monensin and rapamycin treatments on mTOR (mammalian target of rapamycin) signaling pathway-mediated apoptosis and tumor growth in an SH-SY5Y neuroblastoma cell xenograft model. Control, monensin, rapamycin, and monensin + rapamycin groups were formed in the xenograft neuroblastoma model obtained from CD1 nude mice, and tumor volumes and animal weights were recorded throughout the treatment. In xenograft neuroblastoma tumor tissues, apoptosis was determined by TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling) and cleaved-caspase 3 immunohistochemistry, and PI3K (phosphoinositide-3-kinase)/AKT/mTOR expression was determined by the immunohistochemistry and immunofluorescence methods. The combination of monensin and rapamycin was to reduce the growth of xenograft neuroblastoma tumor tissues, trigger apoptosis, and suppress the expression of PI3K/AKT/mTOR. A significant increase in apoptotic cell rate was demonstrated in the combination group, supported by cleaved-caspase 3 immunohistochemistry results. In addition, it was reported that the combination treatment regime triggered apoptosis by reducing the expression of phosphorylated PI3K/AKT/mTOR. Our preclinical results may be a precursor to develop new therapeutic approaches to treat neuroblastoma.